The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/clr.13461
|View full text |Cite
|
Sign up to set email alerts
|

The effect of factors related to periodontal status toward peri‐implantitis

Abstract: Objective To investigate the association between periodontal status and peri‐implant diseases in patients with osseointegrated dental implants of different implant systems. Materials and methods This cross‐sectional study evaluated 200 consecutive implant patients using clinical and radiographic examinations during periodontal maintenance visits. The demographic data and treatment history were obtained from history taking and chart record review. The association between periodontal status and peri‐implant dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
4
33
2
Order By: Relevance
“…In addition to these results, patients who have ≥ 4 number of implants have higher risk for peri-implantitis occurrence (OD = 2.10) than patients having number of implants < 4 as reported in numerous studies [3,22,[33][34][35]. These results are in agreement with the literature as follows: higher PI (which also demonstrates poor oral hygiene) [27,30,36], patients who do not participate to the maintenance therapy [7,37], and patients who had history of periodontitis were demonstrated as risk indicators for the development of peri-implant disease [4,33,38]. In this cross sectional study, patients who have current diagnosis of periodontitis had increased probability for development of peri-implant disease.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to these results, patients who have ≥ 4 number of implants have higher risk for peri-implantitis occurrence (OD = 2.10) than patients having number of implants < 4 as reported in numerous studies [3,22,[33][34][35]. These results are in agreement with the literature as follows: higher PI (which also demonstrates poor oral hygiene) [27,30,36], patients who do not participate to the maintenance therapy [7,37], and patients who had history of periodontitis were demonstrated as risk indicators for the development of peri-implant disease [4,33,38]. In this cross sectional study, patients who have current diagnosis of periodontitis had increased probability for development of peri-implant disease.…”
Section: Discussionsupporting
confidence: 88%
“…Knowledge of the factors that lead to peri-implant disease is crucial for maintaining the dental implants to function properly. Several patient-and implant-related risk indicators including poor oral hygiene, smoking, history of periodontal disease, and compliance of maintenance have been reported [2][3][4]7]. On the other hand, the necessity of keratinized tissue around implant is controversial.…”
mentioning
confidence: 99%
“…The data comprised their medical and dental history, smoking habits, history of periodontal therapy, oral hygiene status, history of implant treatment, and implant prosthesis types. The patients’ clinical and radiographic examinations were performed at one visit as described in a recent publication [ 23 ] and reported thoroughly in the next session. Maintenance care at the implant sites was performed according to the cumulative interceptive supportive therapy (CIST) protocol [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23] The risk for peri-implant bone destruction is increased by the opportunistic infection of adjacent teeth. 24,25 Recent studies demonstrated that higher implant failure is associated with the severity of periodontal disease. 25,26 Thus, a Ti implant surface with resistance to periimplant infection would increase long-term implant survival by decreasing inflammatory bone tissue destruction.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Recent studies demonstrated that higher implant failure is associated with the severity of periodontal disease. 25,26 Thus, a Ti implant surface with resistance to periimplant infection would increase long-term implant survival by decreasing inflammatory bone tissue destruction. This study aimed to investigate whether surface Sr modification also induces favorable osteoblast functions of MSCs under a P. gingivalis LPSstimulated inflammatory condition in a clinical Ti oral implant surface.…”
Section: Introductionmentioning
confidence: 99%